Bioimpedance in Pregnant Women with Preeclampsia - Silva, Elaine Gomes da [UNESP]; Carvalhaes, Maria Antonieta de Barros Leite [UNESP]; Hirakawa, Humberto Sadanobu [UNESP]; Silva, Evelise Guimarães da [UNESP]; Peraçoli, José Carlos [UNESP] (Taylor & Francis Inc, 2010)
To analyze the direct (resistance and reactance) and indirect (intra and extracellular total body water) BIA parameters in preeclamptic women, 51 healthy pregnant women and 65 preeclamptic women were submmited to bioeletric impedance on the thrid trimester of gestation The significance value adopted was 5% Preeclamptic women showed lower values for R (448 Omega vs 542 Omega), Rc (40 Omega vs 53 Omega) and ICW (49 45% vs 51%) when compared to control group They also showed higher values for TBW (49% vs 47%), TBWcor (41 6% vs 34%) and ECW (50% vs 47%) Biolectric impedance allowed differentiating preeclamptic women from health pregnant women, indicating that preeclampsia changes body compartments during pregnancy This method can help understand the mechanisms involved in preeclampsia and to be a prediction away of preeclampsia
Keywords: Bioelectrical impedance; Preeclampsia; Pregnancy; Resistance; Reactance